KARAKTERISTIK ORGANOLEPTIK SOYGHURT EDAMAME SEBAGAI MAKANAN PENDAMPING ALTERNATIF UNTUK PENDERITA STUNTING - Moh. Nu'man Ash Shiddieqiey; Yoan Melly Nurrahma; Anastasya Eka Saputri; Supeno Supeno; Ulin Nuha; Diah Wahyuni; Zainur Rasyid Ridlo; Rusdianto Rusdianto (Jurusan Pendidikan MIPA FKIP Universitas Jember, 2021)
Stunting sufferers in Jember Regency have increased from 17,344 in2018 to 19,870 in 2019. The purpose of this study was to determine the potential ofedamame soyghurt as an alternative complementary food for stunting sufferers. Theexperimental design used was a completely randomized design (CRD) with differentcombinations of treatments on edamame juice, skim milk, and starter. The result wasanalyse of organoleptic include taste, color, aroma, and texture with hedonic testusing 10 panelists non-skilled. Based on the result of organoleptic, the average valueof preference ranges from taste between 3.2-3.4 (slightly like to like), aroma 3.6-3.9(slightly like to like), color 3.1-4.2 (slightly like to like) like), texture 3.5-4 (slightlylike to like). The best treatment was in the combination of edamame soyghurttreatment in the proportions of skim milk 150 (%w/v), edamame juice 730 (%v/v),and sucrose 50 (%w/v) with starter 70 (%w/v).